Curating Contemporary Music Festivals A New Perspective on Music's Mediation - Farnsworth, Brandon (Musik und Klangkultur, 2020)
Contemporary music, like other arts, is dealing with the rise of »curators« laying claim to everything from festivals to playlists - but what are they and what do they do anyway? Drawing from backgrounds ranging from curatorial studies to festival studies and musicology, Brandon Farnsworth lays out a theory for understanding curatorial practices in contemporary music, and how they could be a solution to the field's diminishing social relevance. The volume focuses on two case studies, the Munich Biennale for New Music Theatre, and the Maerzmusik Festival at the Berliner Festspiele, putting them in a transdisciplinary history of curatorial practice, and showing what music curatorial practice can be.